Alzheimer's disease in Down syndrome: An overlooked population for prevention trials. Issue 1 (23rd November 2018) - Strydom, André; Coppus, Antonia; Blesa, Rafael; Danek, Adrian; Fortea, Juan; Hardy, John; Levin, Johannes; Nuebling, Georg; Rebillat, Anne‐Sophie; Ritchie, Craig; van Duijn, Cornelia; Zaman, Shahid; et al.
Abstract: The discovery that adults with Down syndrome (DS) have neuropathological features identical to individuals with sporadic Alzheimer's disease (AD) played a key role in the identification of the amyloid precursor protein gene on chromosome 21 and resulted in the amyloid cascade hypothesis. Individuals with DS have a lifetime risk for dementia in excess of 90%, and DS is now acknowledged to be a genetic form of AD similar to rare autosomal‐dominant causes. Just as DS put the spotlight on amyloid precursor protein mutations, it is also likely to inform us of the impact of manipulating the amyloid pathway on treatment outcomes in AD. Ironically, however, individuals with DS are usually excluded from AD trials. This review will discuss primary and secondary prevention trials for AD in DS and the potential barriers and solutions to such trials and describe the Europe‐wide Horizon21 Consortium to establish a DS‐AD prevention clinical trials network.